2006
DOI: 10.3354/meps325281
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal availability of abundant, energy-rich prey influences the abundance and diet of a marine predator, the Steller sea lion Eumetopias jubatus

Abstract: Steller sea lions Eumetopias jubatus are central-place foragers that forage in the marine environment while using terrestrial sites to rest and care for young. Some terrestrial sites are used seasonally; however, the reasons for doing so are not fully understood. We addressed the hypothesis that seasonal availability of prey influences seasonal abundance and diet of sea lions. We quantified monthly prey availability and sea lion abundance and quarterly diet composition at Benjamin Island in SE Alaska (2001)(20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 44 publications
2
105
0
1
Order By: Relevance
“…Although a number of studies have attempted to determine the fine-scale availability of Steller sea lion prey in the vicinity of rookeries and haulouts (e.g. Mueter & Norcross 2000b, Womble & Sigler 2006, most data are limited in spatial scale or species sampled and confounded by the fact that little is still known of the foraging distribution of Steller sea lions.…”
Section: Steller Sea Lion Diet In Kodiak Archipelagomentioning
confidence: 99%
See 2 more Smart Citations
“…Although a number of studies have attempted to determine the fine-scale availability of Steller sea lion prey in the vicinity of rookeries and haulouts (e.g. Mueter & Norcross 2000b, Womble & Sigler 2006, most data are limited in spatial scale or species sampled and confounded by the fact that little is still known of the foraging distribution of Steller sea lions.…”
Section: Steller Sea Lion Diet In Kodiak Archipelagomentioning
confidence: 99%
“…Given their extremely high energy content (Anthony et al 2000) and local abundance, herring most likely provide an important seasonally predictable and energy-rich prey source in the nonbreeding season. Overwintering and spawning herring have also been noted as important prey for sea lions at a number of locations in southeast Alaska, where their distribution has been shown to influence the spatial distribution and abundance of Steller sea lions (Womble et al 2005, Womble & Sigler 2006. Fine-scale analysis of the spatial and temporal patterns in the diet of Steller sea lions in relation to trends in their use of terrestrial haulouts would greatly improve our understanding of the foraging behavior of this species and may assist in assessing what proportions of the population are utilizing particular prey resources.…”
Section: Steller Sea Lion Diet In Kodiak Archipelagomentioning
confidence: 99%
See 1 more Smart Citation
“…While considerable effort has been expended to understand the seasonal nutritional requirements for individual W-SSLs [22][23][24], less is known about the size of local, seasonal prey populations required to support the recovery of W-SSL populations. For instance, the abundance of pollock, Pacific cod, Atka mackerel, and other prey necessary for central Aleutian Islands W-SSLs during the winter and early spring [25,26] is not simply limited to the fish they consume, but also includes the much larger number of fish necessary in the environment to guarantee successful foraging [27][28][29]. Womble et al [27] and Sigler et al [29] concluded that the relationship between Steller sea lion abundance at seasonal haulouts and local prey biomass (e.g.…”
Section: Implications For the Aleutian Islands Pollock Fisherymentioning
confidence: 99%
“…For instance, the abundance of pollock, Pacific cod, Atka mackerel, and other prey necessary for central Aleutian Islands W-SSLs during the winter and early spring [25,26] is not simply limited to the fish they consume, but also includes the much larger number of fish necessary in the environment to guarantee successful foraging [27][28][29]. Womble et al [27] and Sigler et al [29] concluded that the relationship between Steller sea lion abundance at seasonal haulouts and local prey biomass (e.g. temporary spawning aggregations) is exponential: more prey energy per sea lion is necessary as the number of sea lions increases as…”
Section: Implications For the Aleutian Islands Pollock Fisherymentioning
confidence: 99%